PTH-111 IBD Nurse led rapid referral pathway for suspected IBD – is it effective?. Issue 2 (June 2019) - Posso, Jessica; Cambridge, Vanessa; Walker, David
Abstract : Introduction: Recommendations from the UK IBD Standards Group stress the importance of adequate referral pathways in maintaining a high quality of clinical care. In 2016 the gastroenterology department at the Royal United Hospital Bath developed a new rapid referral pathway for suspected inflammatory bowel disease (IBD) patients in order to improve patient care. All GP referrals for suspected IBD were evaluated by a gastroenterology consultant. The clinical information together with any available blood and stool results were reviewed. Symptomatic patients with a suspected new diagnosis of colitis were triaged to an urgent IBD nurse appointment (within 4 weeks) and if appropriate, an urgent flexible sigmoidoscopy with the IBD nurse was offered later the same day. Those patients with a new diagnosis of IBD were given treatment and educational information post procedure. The primary aim of the study was to assess the effectiveness of the new rapid referral pathway and to see if it could be improved further. Methods: A retrospective review was performed of all suspected IBD referrals that had been triaged to an urgent IBD nurse appointment over a 1 year period. For each case identified, a structured proforma review was performed using the original GP referral, the patient's medical notes, blood profile, stool analysis, endoscopy report and histology. Results: 30 patients were referred via the rapid access pathway over a 1 year period. All 30 patients had a flexible sigmoidoscopy with biopsies performed. 30% (9/30) had a new diagnosis of IBD [8 UC, 1 IBD-U], 3% (1/30) had diverticulitis and 67% (20/30) had a normal procedure. In 93% of cases bloods including a FBC & CRP had been performed at the time of referral. However stool microscopy was only performed in 60% of cases and a faecal calprotectin (FC) in 37%. 83% of patients were seen within 4 weeks and all patients were seen within 6 weeks. Conclusions: At the Royal United Hospital Bath, there has been a significant year on year increase in the number of 2WW referrals which has negatively impacted on the ability to see suspected IBD patients within the recommended 4 week period. The new IBD nurse led rapid access pathway resulted in 83% of suspected IBD patients being reviewed within 4 weeks and all suspected IBD patients being reviewed within 6 weeks. Interestingly, only 30% of patients were found to have a new diagnosis of IBD. The study showed that FC testing was only happening in a minority of cases. The importance of FC testing has since been highlighted at educational meetings with local GPs and a more rigid IBD referral proforma has been developed. This study shows that an IBD nurse led rapid referral pathway can improve the patient experience by facilitating a quicker diagnosis of IBD and enhances continuity of care.